Credit card holders in Malaysia: customer characteristics and credit card usage - Hussin, Siti Rahayu; Kassim, Salina; Jamal, Nuraien (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
As an effort to profile credit card users in Malaysia, this study seeks to examine the relationship between credit card users’ characteristics (demographics and socio-economic factors) and credit card usage. Using a convenient sampling method, a survey was conducted on 350 credit card holders in the Klang Valley, Malaysia. Customer background includes gender, age, occupation, and monthly gross income. The credit card usage was measured by items constructed specifically for this research which is adopted from past studies on credit card. Descriptive analysis is used to describe the customers’ background and credit card usage, while the relationship between consumer characteristics and credit card usage is being assessed empirically using cross tabulation/chi-square and ANOVA. The findings of this study revealed that there are significant differences in credit card usage among credit card holders of different personal background. However, simple t-tests showed there is no significant difference in credit card usage among users of different gender. This study has significance in terms of providing useful information for developing customer profile and revising credit card promotional strategies.